Effects of Flow Velocity on the Dynamics of Juvenile Fish Habitats in River Meanders of the Irtysh River - Andrey A. Chemagin; Elena I. Popova; Martin Schletterer (Diversity)
Understanding the spatial distribution of freshwater fish in heterogeneous aquatic environments is crucial for understanding riverine ecosystems and the rational use of aquatic biological resources. This study investigates the distribution patterns of juvenile fish in the lower reaches of the Irtysh River, including hydrodynamic conditions during different water level regimes. With hydroacoustic surveys, we assessed fish density and distribution in two wintering riverbed depressions during the spring flood and summer low water period. The main fish aggregations consisted of Cyprinidae and Percidae, with juveniles predominantly occupying areas with reduced flow velocities (0.15–0.75 m s−1). Correlation analysis showed strong direct relationships between the area occupied by juvenile carp and perch and zones with specific flow velocities. The study highlights that hydrodynamic characteristics, particularly flow velocity, are key factors influencing the distribution and aggregation of juvenile fish. These findings underscore the importance of considering hydrodynamic factors and species-specific traits in understanding fish distribution patterns and in managing freshwater ecosystems effectively. This research contributes to the understanding of the multifunctional roles of riverbed depressions in supporting juvenile fish populations and emphasizes the importance of hydroacoustics to predict fish distributions in dynamic aquatic environments.